Working procedure for SEP and key problems in practice - Yufeng YAO (Dianxin kexue)
The working procedure for SEP was analyzed，patent disclosure policy and FRAND principle of SSO were described.Based on the actual case analysis，some key problems of SEP in practice were analyzed，including patent licensing rates，relief under FRAND principle，antitrust law regulation of the abuse of SEP.